(untitled) (Eureka Journal of Language, Culture & Social Change, 2025)
Today, along with many other spheres, many reforms are being carried out in the sphere of culture and art. In particular, the issue of enhancing the role of theatrical art in the social life of society, attracting our people to theaters, is at the center of attention. This article presents analytical considerations and recommendations on the socio-functional characteristics of Uzbek theatre.